Sheffield Clinical Research Fellowship programme: a transferable model for UK gastroenterology. Issue 4 (6th December 2017) - Kurien, Matthew; Hopper, Andrew; Lobo, Alan J; McAlindon, Mark E; Sidhu, Reena; Gleeson, Dermot C; Hebden, John M; Basu, Kumar; Panter, Simon; Lockett, Melanie; Sanders, David S
Abstract : Out of programme (OOP) opportunities are to be encouraged. This article gives an insightful view of the Sheffield Clinical Research Fellowship Programme. Unique trainee feedback is provided. The take home message is clear - trainees should grab OOP experiences with both hands! For consultants the logistics described are potentially transferrable to their own regions.